Adaptive evolution of peptidoglycan recognition protein family regulates the innate signaling against microbial pathogens in vertebrates. (October 2020) - Ahmad, Hafiz Ishfaq; Asif, Akhtar Rasool; Ahmad, Muhammad Jamil; Jabbir, Farwa; Adnan, Muhammad; Ahmed, Shakeel; Afzal, Gulnaz; Saleem, Ali Haider; Li, Linmiao; Jiang, Haiying; Simirgiotis, Mario Juan; Rauf, Mubashar; et al.
Abstract: The innate immune system is the first line of defense in vertebrates against microbial pathogens. This defense system depends on the peptidoglycan pathogen recognition of receptors (PGRPs) existing in both invertebrates and vertebrates. Although some studies revealed the structural and functional differences between them, however, the evolutionary history and the selection pressures on these genes during adaptive evolution are poorly understood. In this study, we examined four (PGLYRP1, PGLYRP2, PGLYRP3, and PGLYRP4) genes of 127 vertebrates' species, conserved across vertebrates to evaluate positive selection pressure drives by adaptive evolution. The codons under positive selection were recognized through likelihood tests by comparing different models based on ω ratios in these genes across the vertebrate species. The positive selection test used two sets of models M1a vs. M2a and M7 vs. M8. The results showed that the test of these genes in M1a vs. M2a was not significant with the likelihood value 2ΔlnL = 0, while the likelihood ratios ( 2ΔlnL ) were 2ΔlnL = 12.386, 2ΔlnL = 4.9283, 2ΔlnL = 24.031, and 2ΔlnL = 103.39 for PGLYRP1, PGLYRP2, PGLYRP3, and PGLYRP4 in M7 vs. M8, respectively. Our study identified the evidence of robust positive selection for these four genes across the vertebrates. These protuberant changes in PGRPs evolution of vertebrates reveal their role in innate immunity. Our study provides an insight based on PGRP genes to understand the evolution of host and pathogens interaction that leads to the progress of the novel conducts for immune diseases that include proteins linked to the recognition of pathogens. Highlights: The positive selection of PGRP genes in host adaptation during evolution in response to bacterial pathogens. The selection pressure on PGRP genes cause modification in protein structure during adaptive evolution that increased the immunity against bacterial pathogens in vertebrates. These protuberant changes in PGRPs evolution of vertebrates reveals their role in innate immunity against pathogens. This study helps to understand the evolution of host-pathogens interaction for immune diseases that include proteins linked to the recognition of pathogens.